2014
DOI: 10.1542/peds.2013-0846
|View full text |Cite
|
Sign up to set email alerts
|

Dental Caries and Growth in School-Age Children

Abstract: BACKGROUND AND OBJECTIVE: Dental caries in young children is commonly untreated and represents a public health problem. Dental caries in children is reported to affect their anthropometric outcomes, but the evidence is conflicting. Some studies found no association, whereas others found that caries was associated with underweight or overweight. The objective was to assess the relationship between dental caries status and height and weight in 6- to 8-year-old Saudi children with high caries pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
118
3
15

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(143 citation statements)
references
References 34 publications
7
118
3
15
Order By: Relevance
“…This scenario presupposes that caries was an agent of natural selection before the development of modern dentistry (8,45). We think that this is not unlikely, given the known acute consequences of caries, such as the increased risk of abscess (46) and chronic consequences increase in difficulty eating, particularly in children, and reduced weight/height gain (47,48). Nevertheless, hypotheses about the agents of evolutionary change in humans are very difficult to prove, and we note that, given DMBT1 SAG protein is expressed on other mucosal epithelia and interacts with other microbes, other evolutionary scenarios are possible, such as adaptation to an altered microbiome of the gut.…”
Section: Discussionmentioning
confidence: 99%
“…This scenario presupposes that caries was an agent of natural selection before the development of modern dentistry (8,45). We think that this is not unlikely, given the known acute consequences of caries, such as the increased risk of abscess (46) and chronic consequences increase in difficulty eating, particularly in children, and reduced weight/height gain (47,48). Nevertheless, hypotheses about the agents of evolutionary change in humans are very difficult to prove, and we note that, given DMBT1 SAG protein is expressed on other mucosal epithelia and interacts with other microbes, other evolutionary scenarios are possible, such as adaptation to an altered microbiome of the gut.…”
Section: Discussionmentioning
confidence: 99%
“…En Colombia se han reportado cifras variables, llegando a afectar más de tres cuartas partes de los niños y niñas evaluados en algunos de estos estudios [4][5][6][7], con diferentes niveles de severidad. Este problema de salud bucal es motivo de preocupación, por cuanto se tiene evidencia de que compromete el bienestar, la calidad de vida y el adecuado crecimiento y desarrollo de niños y niñas [8][9][10][11][12][13].…”
Section: Introductionunclassified
“…Most research on this relationship has been conducted in populations with caries and compromised pulp in communities whose caries prevalence is 87.1% 9 and 82.3%.…”
Section: With Cariesmentioning
confidence: 99%
“…8 It has been reported that advanced caries produce pain, irritability and disturbance in sleep, affecting the quality of life of children and potentially leading to impaired secretion of growth hormone. 9 Infection and inflammation caused by caries result in increased energy expenditure and metabolic demand, and can lead to a decrease in micronutrients. 9 Levels of glucocorticoids increase in response to pain caused by tooth infection, 10 producing an alteration in neurogenesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation